Environmental assessment tool to analyse the presence of critical and valuable raw materials. (2016) - Bachiller, Patricia Gómez; Pina, Carmelo; Elduque, Daniel; Clavería, Isabel; Javierre, Carlos; Sarasa, Judith
The aim of this paper is show the software 'Sustainable Electronics' (SE), developed in the University of Zaragoza as an environmental impact assessment tool, specially developed to design components taking into account the presence of critical and valuable raw materials consumption; simulating environmental impact and measuring the overall raw material consumption, taking into account material composition of the electronic components. It considers raw material acquisition, manufacturing processes, transports and end of life. This software allows us to easily update and use the datasets provided by Life Cycle Inventory databases, such as, for example, EcoInvent, developed by the Swiss Centre for Life Cycle Inventories. The methodology has been tested through the software in an electronic board of a touch control used in an induction hob. As result, it has been obtained that there is a high consumption of materials such as copper, tin or aluminium.